Relationship between winter orographic precipitation with synoptic and large-scale atmospheric circulation: The case of mount Olympus, Greece - Styllas, Michael Nikolaos; Kaskaoutis, Dimitrios (Bulletin of the Geological Society of Greece, 2018)
The relationship between the winter (DJFM) precipitation and the atmospheric circulation patterns is examined around Mount Olympus, Greece in order to assess the effects of orography and atmospheric dynamics over a small (less than 100 x 100 km) spatial domain. Winter accumulated rainfall datasets from 8 stations spread along the eastern (marine) and western (continental) sides of the Mount Olympus at elevations between 30 m and 1150 m are used during the period 1981 to 2000. Synoptic scale conditions of mean sea-level pressure and geopotential heights at 850 hPa and 500 hPa, were used to explain the multiyear rainfall variability. High pressure systems dominated over the central Mediterranean and most parts of central Europe during the late 1980’s and early 1990’s, are associated with minimum winter rainfall along both sides of Mount Olympus. The winter of 1996 was associated with peak in rainfall along the marine side of the mountain and was characterized by enhancement of upper level trough over the western Mediterranean and increased low tropospheric depressions over the southern Adriatic and the Ionian Seas. This atmospheric circulation pattern facilitated a southeasterly air flow that affected more (less) the marine (continental) sides of the mountain. In contrast, dominance of low pressure systems with cores over the Gulf of Genoa and the Central Mediterranean affect the study area mostly from west/southwest revealing higher correlations with the precipitation in the continental side of the mountain (r= -0.80; Elassona station) and considerably lower correlations with the marine side (r = -0.67; Katerini station). This highlights the orographic barrier of the Mount Olympus revealing large differences between the upward and leeward sides. Large scale atmospheric patterns like the North Atlantic Oscillation and the Arctic Oscillation seem to influence the winter rainfall in the lowlands along the continental side of the mountain.